(untitled) (The Agriculturists, 2010)
A laboratory experiment was conducted at the Bangladesh Rice Research Institute, Gazipur during 2003 to determine phosphorus (P) desorption characteristics for 10 acid piedmont rice soils of Bangladesh. Soil samples were analyzed for sand, silt and clay, pH, organic carbon, available P, Mehlich-3 (M3) extractable P and dithionite extractable Fe (FeD). Desorption of phosphorus (release pattern) from different soils varied from 1.34 to 19.17 ppm. Phosphorus desorption was affected by the increased shaking time up to one hour. In almost all the studied soils, the highest desorbed P was extracted at one hour shaking time, beyond which there was again re-adsorption in most of the soils. Soil properties, particularly, pHKCl, ?pH, organic carbon and clay content were found to be important soil variables in determining phosphorus desorption in piedmont soils. The increase in ?pH and organic carbon increased P desorption, while an increase in clay and Fe tended to decrease in P desorption. Equations were proposed for predicting ?, ?, and K of famous Sharpleys equation and were tested for better prediction of P desorption in Piedmont soils of Bangladesh. Sharpleys equations for Piedmont soils resulted in a strong relationship (R2 = 0.86) between measured and predicted P desorption. The equations recommended by Sharpley to predict values for ?, ? and K has provided a good prediction of P desorption for our Piedmont rice soils.